2018
DOI: 10.1155/2018/6589608
|View full text |Cite
|
Sign up to set email alerts
|

Danshen-Honghua Ameliorates Stress-Induced Menopausal Depression in Rats

Abstract: Objective Previously, we have shown that Danshen-Honghua (DSHH) for cognitive deficits after ischemia induced impairments of the hippocampus. Here, we investigate the effects of DSHH on stress-induced depression in menopausal rats. Methods A rat model with menopausal depression was established with bilateral ovariectomies in female SD rats followed by chronic mild stress treatment for 21 days. 40 rats were randomly divided into the sham surgery group (sham surgery and no stress treatment), surgery group (surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
(24 reference statements)
2
10
0
Order By: Relevance
“…Our results showed that UCMS significantly decreased body weight and increased the CORT, which is consistent with our previous reports (Fig. 1E, F ) (Gu et al 2018a , b ). These results indicate that UCMS caused depression-like behaviors.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…Our results showed that UCMS significantly decreased body weight and increased the CORT, which is consistent with our previous reports (Fig. 1E, F ) (Gu et al 2018a , b ). These results indicate that UCMS caused depression-like behaviors.…”
Section: Resultssupporting
confidence: 94%
“…Group III started from the third week and were given continuous intragastric drug administration for 3 weeks continuously, 3 times a day. Fluoxetine solution was dissolved in 0.9 % saline (Gu et al 2018b ). Rats in group II and group III were exposed to consecutive UCMS for 5 weeks, while rats in group I were exempt.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies show that monoaminergic neurotransmission involving 5-HT, NE and DA exerts major influence on brain circuits by regulating mood, reactivity to psychological stress, self-control, motivation, drive, and cognitive performance [25]. Studies also showed that the levels of DA and 5-HT decreased in the hypothalamic tissue of patients with depression [26].…”
Section: Discussionmentioning
confidence: 99%
“…Higher circulating levels of LH and FSH were attributed to decreased negative feedback on estrogen release. Some studies report that high levels of LH and FSH were associated with depression (Gu et al., 2018; Soares, 2016). According to Freeman (2010), depressive symptoms were significantly associated with greater variability in FSH and estradiol levels.…”
Section: Discussionmentioning
confidence: 99%